Data dictionary template for research dataset - Ghazali, Saadiah; Roslan, Shazleen (WorldFish, 2024)
This template functions as a centralized document that defines and describes the elements within a dataset, providing detailed information about each data field, including its name, type, format, allowed values, and relationships with other data elements, ultimately ensuring consistency and accurate interpretation of data across an organization or project. An example shown in this template is taken from a PesKaas published dataset.